Alternating time spent on social interactions and solitude in healthy older adults. (11th August 2022) - Luo, Minxia; Pauly, Theresa; Röcke, Christina; Hülür, Gizem
Abstract: Time spent on being with others (social interactions) and being alone (solitude) in day to day life might reflect older adults' agentic regulatory strategies to balance the needs to belong and to conserve energy. Motivated from a joint lifespan psychological and social relationship theoretical perspective, this study examined how time spent on social interactions and solitude alternatively unfolds within individuals in daily life, relating to individual differences in trait‐level well‐being and fatigue. Over 21 days, a total of 11, 172 valid records of social interactions were collected from 118 older adults (aged 65–94 years) in a smartphone‐based event‐contingent ambulatory assessment study in Switzerland. On average, a social interaction episode lasted 39 min and a solitude episode lasted 5.03 hr. Multilevel models showed that, at the within‐person level, a longer‐than‐usual social interaction preceded and was followed by a longer‐than‐usual solitude episode. Moderator analyses showed that older adults with higher trait life satisfaction and lower trait fatigue spent even more time in social interactions after longer solitude episodes, amplifying the solitude‐then‐interaction association. Our findings suggest that whereas social interaction is a means to improve well‐being, solitude is also an integral part in older adults' daily life supporting energy recovery.